Oil booms and inequality in Iran. Issue 2 (14th November 2018) - Farzanegan, Mohammad Reza; Krieger, Tim
Abstract: We study the response of income inequality to positive per capita oil and gas revenue shocks in Iran. Using historical data from 1973 to 2016 and vector autoregression (VAR) as well as vector error correction (VECM) model‐based impulse‐response functions, we find a positive and statistically significant response of income inequality to oil booms. We also explore possible channels through which oil booms may increase inequality, including private sector credit growth, construction investment, international trade (imports) and real economic output. We find that following an oil boom, higher imports, private sector credit growth, and real economic output can explain the increased income gap to a certain degree in Iran's oil‐based economy. Our analysis can help policymakers evaluate and accommodate the possible positive or negative effects of inequality in Iran resulting from the 2016 lifting of the embargo against the country.